2014
DOI: 10.3748/wjg.v20.i15.4208
|View full text |Cite
|
Sign up to set email alerts
|

Role of cetuximab in first-line treatment of metastatic colorectal cancer

Abstract: The treatment of metastatic colorectal cancer (mCRC) has evolved considerably in the last decade, currently allowing most mCRC patients to live more than two years. Monoclonal antibodies targeting the epidermal growth factor receptor (EGFR) and vascular endothelial growth factor play an important role in the current treatment of these patients. However, only antibodies directed against EGFR have a predictive marker of response, which is the mutation status of v-Ki-ras2 Kirsten rat sarcoma viral oncogene homolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 83 publications
0
15
0
Order By: Relevance
“…Evaluation of other measures of tumor response may inform clinical decision-making (although such measures require further prospective confirmation; ref. 40). Depth of tumor response was significantly greater and likelihood of achieving a !30% reduction in tumor dimensions within 8 weeks of treatment was significantly higher in panitumumab patients.…”
Section: Discussionmentioning
confidence: 98%
“…Evaluation of other measures of tumor response may inform clinical decision-making (although such measures require further prospective confirmation; ref. 40). Depth of tumor response was significantly greater and likelihood of achieving a !30% reduction in tumor dimensions within 8 weeks of treatment was significantly higher in panitumumab patients.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that about 25% of patients with CRC are clinically diagnosed with liver metastasis at the initial diagnosis, and approximately 50% of patients with CRC develop symptoms of liver metastasis during the course of their disease. Around 30% to 50% of patients with CRC display recurrent liver metastasis after radical resection and more than 50% succumb to the disease . However, the current therapies for patients with CRC live metastasis, including surgery, radiotherapy, and chemotherapy treatment in the CRC metastasis, remain unsatisfactory due to rapid CRC metastasis deterioration and drug resistance …”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that biologic agents with FOLFOX /FORFIRI can significantly improve the therapeutic effect compared with FOLFOX /FORFIRI alone. [14] Their role in wild-type KRAS mCRC as the first-line therapy, however, has not been systematically examined. For this review, cetuximab was defined as a drug targeting a specific receptor of cancer cell growth factors, epidermal growth factor receptor (EGFR).…”
Section: Introductionmentioning
confidence: 99%